LEADERSHIP DEFICIENCIES AS BARRIERS TO ORGANIZATIONAL CHANGE IN FITNESS CENTERS: A QUANTITATIVE ANALYSIS OF ADAPTATION AND GROWTH IMPEDIMENTS - Zanfir Ciprian; Iconomescu Teodora Mihaela; Talaghir Laurențiu-Gabriel (Sport şi Societate)
Fitness centers are compelled to evolve by integrating innovative fitness modalities, adopting digital platforms, and responding to the growing demand for personalized wellness experiences.The research employed a structured questionnaire, to collect data on leadership behaviors, change management practices, and organizational outcomes.The questionnaire was designed to capture the multifaceted aspects of leadership deficiencies and theirimpact on organizational change.To ensure the statistical robustness of the study and the validity of the findings, a rigorous sampling process was undertaken.The findings of this study illuminate the significant impact of leadership deficiencies on organizational change processes within fitness centers. The low effectiveness of leadership communication, with only 22% rated as effective, impedes the dissemination of strategic goals and change initiatives.This study provides robust quantitative evidence that leadership deficiencies serve as significant barriers to organizational change in fitness centers. The findings reveal those shortcomings in leadership competencies-particularly in communication, decision-making, and vision articulation-substantially impede adaptation and growth.Future research could explore the effectiveness of specific leadership development interventions on organizational change outcomes and examine the role of middle management in facilitating change and bridging the gap between top leadership and frontline employees